Dosimetric and radiobiological evaluations as well as technical aspects of left breast treatment employing DIBH with SGRT in radiotherapy with IMRT step and shoot, IMRT Dynamic MLC and VMAT - Julien Rolland; Stéphane Payan; Pierre Fau; Hugues Mailleux; Agnès Tallet (Journal of Applied Clinical Medical Physics, 2026)
Abstract Background Treatment of the left breast using deep inspiration breath hold (DIBH), combined with surface guided radiotherapy (SGRT), has emerged as the standard for reducing the dose to the heart, the left anterior descending coronary artery (LAD), and the ipsilateral lung. Since this treatment is administered during breath hold (BH) phases, it is beneficial to limit the duration of delivery to improve patient comfort. Furthermore, the SGRT signal can be disrupted when the gantry passes in front of the left SGRT camera during the delivery with volumetric modulated arc therapy (VMAT), which complicates the treatment process. In contrast, using a simpler treatment plan with two tangential beams with intensity modulated radiation therapy (IMRT) helps avoid this difficulty. For image guided radiotherapy (IGRT) as well, monitoring becomes more complex with the addition of the imaging panel and the X‐ray tube for the SGRT signal. Purpose This study compares dosimetric and radiobiological differences between two methods in IMRT step and shoot (SS‐IMRT) or dynamic multileaf collimator (DMLC‐IMRT) using two tangential beams and VMAT with two arcs. Methods Twenty left breasts were planned using SS‐IMRT, DMLC‐IMRT and VMAT. The comparison is based on dosimetric criteria at target (D 95% , homogeneity index (HI), conformity index (CI)) and doses to organs at risk (OARs). Radiobiological parameters (tumor control probability (TCP), normal tissue complication probability (NTCP) and second cancer complication probability (SCCP)) and plan data such as MLC modulation, QA results, and delivery time were also compared. A Wilcoxon signed‐rank test was performed between each method. Results The results are listed for SS‐IMRT, DMLC‐IMRT and VMAT, respectively. For the PTV: D95% 37.5 Gy, 38.3 Gy, 38.4 Gy ( p < 0.05 DMLC‐IMRT & VMAT vs SS‐IMRT); CI 0.74, 0.76, 0.83 ( p < 0.05); HI 0.15, 0.11, 0.11 (p > 0.05). TCP: 91.2%, 92.2% and 92.9% ( p < 0.05). For OARs; heart: D mean 0.8 Gy, 1.0 Gy, 1.2 Gy ( p < 0.05); LAD: V 10Gy 0.5%, 0.1%, 0.0% ( p < 0.05 except DMLC‐IMRT vs VMAT); ipsilateral lung: D mean 5.0 Gy, 4.8 Gy, 5.7 Gy ( p < 0.05), V 5Gy 19.4 %, 18.6 %, 25.7%. NTCP pericarditis: 0% for all techniques. NTCP pneumonitis: 4.1%, 3.7%, 2.2%; contralateral lung: D mean 0.3 Gy, 0.5 Gy, and 0.9 Gy; contralateral breast: D mean : 0.6 Gy, 0.7 Gy and 1.2 Gy, V 3Gy 0.6%, 0.4%, 1.7% ( p < 0.05), SCCP: 0.4%, 0.5%, 0.9%. Plans data: more modulated in DMLC‐IMRT but QA results remained satisfactory. The average delivery times are 95.4s, 81.6s, 141.7s. Conclusions In most cases, choosing DMLC‐IMRT will result in a plan similar to VMAT and superior to SS‐IMRT. Compared to SS‐IMRT, DMLC‐IMRT delivers a slightly higher dose to contralateral OARs, with a slight increase in the risk of radiation‐induced cancer, but lower than VMAT. The main advantage is that it eliminates camera occlusion issues, which can lead to erroneous SGRT signals during treatment and IGRT verification. DMLC‐IMRT reduces treatment time by an average of 42% compared to VMAT, which will remain the solution for the most complex morphologies.